Hema e-Chart: Italian Registry for prospective analysis of epidemiology, management and outcome of febrile events in patients with hematological malignancies - Pagano, L; Caira, M; Nosari, A; Rossi, G; Locatelli, F; Viale, P; Aversa, F (Journal of chemotherapy (Florence), 2010)
The aim of the study was to create a prospective computerized registry to collect and analyze febrile events, particularly due to fungal infections, in patients with hematological malignancies. A systematic approach that starts from the registration of new diagnosis and complete follow-up can be of help for the study of treatment and evolution of these complications. The software allows several concurrent users to create and manage medical information in a website. Its aim is to improve the speed, quality and integration of information related to subjects with febrile event, ultimately resulting in improving patients' care.Patients included adults and children with acute and chronic myeloid or lymphoid leukemia, Hodgkin's and non-Hodgkin's lymphoma, myelodysplastic syndrome, or multiple myeloma. The registry also included data regarding event onset in hematopoietic stem cell transplants (HSCTs). In order to evaluate the incidence of febrile events, all new diagnoses of hematological malignancy and all HSCTs were reported.The Hema e-Chart can be a very useful network collecting information about febrile events in patients with hematological malignancy and HSCTs. Significant trends and treatment practices are expected to be observed. As enrollment continues, data will be analyzed and published, which will provide valuable information concerning the epidemiology, therapy, and outcome of infectious complications.